Project to digitize collections in national information institutions: case of Algerian National Library - Fadila BENTAHAR & Kamel BOURABIA (Akofena)
Abstract: The National Library is an important cultural and scientific building in Algeria, as it is one of the oldest cultural institutions, dating back to 13 October 1835. One of its main missions is to collect, preserve and disseminate the national heritage in all media, as well as to collect manuscripts, coins, medals and documents. In the face of the digital revolution, the National Library has set itself the goal of digitizing its collections, and its first attempts have begun with the process of photographing either a few pages of manuscripts or the entire manuscript, depending on the request. However, the National Library faces a number of difficulties in the digitization process, namely the lack of material and financial resources needed to achieve this and thus preserve intellectual production in the best conditions.